Turning adversity to advantage : a history of the Lipan Apaches of Texas and northern Mexico, 1700-1900 - Minor, Nancy McGown (University Press of America, 2009)
This book tells the story of the Lipan Apaches, once one of the largest and most aggressive tribes of the Rio Grande region. The story of the history of the Lipan Apaches is a tale of survival and preservation in the face of incredible challenges.